PENGEMBANGAN GAME EDUKATIF : PETUALANGAN OPERASI PECAHAN BERBANTUAN GENIALLY UNTUK KELAS IV SEKOLAH DASAR - Sidik, M. Dian; Refiona Andika; Fadilla Suciana; Salamini S (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a development research that aims to produce a product in the form of an educational game on the material of addition and subtraction operations of fractions in grade IV Elementary School. The development model used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SDN 20 Indarung with research subjects of 27 grade IV students. The results of the effectiveness test of educational games at SDN 20 Indarung obtained a high category with a total of 0.711 in the first meeting and 0.724 in the second meeting. Based on the above findings, it can be concluded that the developed educational game is very suitable for use as a learning medium in grade IV Elementary School.